2023
DOI: 10.1093/eurheartj/ehad344
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan in heart failure with mildly reduced or preserved ejection fraction: a pre-specified participant-level pooled analysis of PARAGLIDE-HF and PARAGON-HF

Abstract: Background and aims The PARAGLIDE-HF trial demonstrated reductions in natriuretic peptides with sacubitril/valsartan compared with valsartan in patients with heart failure (HF) with mildly reduced or preserved ejection fraction who had a recent worsening HF event, but was not adequately powered to examine clinical outcomes. PARAGON-HF included a subset of PARAGLIDE-HF-like patients who were recently hospitalized for HF. Participant-level data from PARAGLIDE-HF and PARAGON-HF were pooled to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…Therefore, the efficacy of HF therapies needs to be evaluated in the context of the total HFH burden. Late clinical trials, such as the PARAGON‐HF trial, the DELIVER trial, and the EMPEROR‐Preserved trial, which included recurrent HF events as an endpoint in their analyses, have found that angiotensin receptor‐neprilysin inhibitors and sodium‐glucose cotransporter 2 inhibitors reduce the overall HFH burden in patients with HFpEF 18–21 . HF is a complex clinical syndrome, and a single risk factor cannot accurately quantify the prognostic risk of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the efficacy of HF therapies needs to be evaluated in the context of the total HFH burden. Late clinical trials, such as the PARAGON‐HF trial, the DELIVER trial, and the EMPEROR‐Preserved trial, which included recurrent HF events as an endpoint in their analyses, have found that angiotensin receptor‐neprilysin inhibitors and sodium‐glucose cotransporter 2 inhibitors reduce the overall HFH burden in patients with HFpEF 18–21 . HF is a complex clinical syndrome, and a single risk factor cannot accurately quantify the prognostic risk of patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is less evidence to support the benefit of RAASi in patients with HFpEF. However, in those with an LVEF <60%, the use of an MRA, ARNi, or angiotensin II receptor blockers (when an ARNi is not feasible) may be considered [34,35].…”
Section: Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%
“…Furthermore, clinical outcomes including mortality and readmission associated with escalation and de‐escalation of medical therapy could be analysed utilizing an EHR‐embedded GDMT score. Lastly, as evidence grows for the implementation of SGLT2i, MRA, and ARNI in HF with preserved/mildly reduced ejection fraction populations, the development of a composite score for non‐HFrEF patients could be the basis for future implementation work 8–11 . In this initial iteration of the score, medication intolerance was not factored in the tabulation of scores.…”
Section: Figurementioning
confidence: 99%